Centro materno infantil en Villa el Salvador - La Rosa de los Ríos, Sebastián Francisco (2020)
Currently, Peru has one of the highest rates of maternal deaths in the region. This generates low trust between foreign investors. It is crucial to invest in health and, particularly, in women's health. It is for this reason that this thesis seeks to provide a solution to the serious lack of maternal and child centers from a technical and architectural point of view. The document is a compilation of information on the subject of health, infrastructure, history and especially the current reality of the health system for women and children. In addition, it is a guideline of techniques, regulations and models of how to make a center of this kind in an economically feasible way.